2010
DOI: 10.1088/0957-4484/21/28/285603
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and conductivity enhancement of Al-doped ZnO nanorod array thin films

Abstract: Al-doped ZnO (AZO) nanorod array thin films with various Al/Zn molar ratios were synthesized by chemical bath deposition. The resultant AZO nanorods were well-aligned at the glass substrate, growing vertically along the c-axis [001] direction. In addition, they had an average diameter of 64.7 +/- 16.8 nm and an average length of about 1.0 microm with the structure of wurtzite-type ZnO. Analyses of energy dispersive x-ray spectra and x-ray photoelectron spectra indicated that Al atoms had been doped into the Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
53
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 38 publications
7
53
0
Order By: Relevance
“…The existence of Al in the ZnO lattice may influence the attractive forces between the atoms and thus reduce the diameter sizes of the ZnO nanorod. A similar behaviour of the decrease in diameter was also reported by Hsu et al (Hsu & Chen, 2010). We also observed that the diameter sizes of Al-doped ZnO nanorods were smaller than those of nanorods produced using a solution that was sonicated in a volume of 1000 ml, as discussed in section 5.1 and 5.2.…”
Section: Aluminium Doping Effectssupporting
confidence: 89%
“…The existence of Al in the ZnO lattice may influence the attractive forces between the atoms and thus reduce the diameter sizes of the ZnO nanorod. A similar behaviour of the decrease in diameter was also reported by Hsu et al (Hsu & Chen, 2010). We also observed that the diameter sizes of Al-doped ZnO nanorods were smaller than those of nanorods produced using a solution that was sonicated in a volume of 1000 ml, as discussed in section 5.1 and 5.2.…”
Section: Aluminium Doping Effectssupporting
confidence: 89%
“…This result is in fairly good agreement with experimental work reported by others. 26 On surface SEM images, undoped and Al-doped ZnO thin films exhibited uniform surface morphology. This clearly reveals that the Al-doped ZnO film was formed by a larger number of denser nanosize grains as compared with the pure ZnO thin film.…”
Section: Resultsmentioning
confidence: 97%
“…Among them, Al -doped ZnO (AZO) nanostructures are capable of reaching the highest conductivity. 10 It is possible to increase the device performance by doping Al in ZnO nanostructures.…”
Section: Introductionmentioning
confidence: 99%